Act 174 : students’ empowerment and it’s implications to UiTMCT / Azahari Abdul Aziz … [et al.] - Abdul Aziz, Azahari; Wan Musa, Wan Mardiana; Misnan, Noorimah; Harun, Shahariah (2021)
Student Empowerment has been discussed at various level of higher education system for quite some time. Unfortunately, the concept and scope of empowerment have never been clearly explained and understood by the administration of the universities. In 2010 UiTMCT has begun its first move in introducing the concept by strategizing various steps to implement the concept. The concept of emphasizing on student decision making in various areas including residential placement and policies imposed on clubs. Institut Pemimpin Muda (IPM) was established to enhance the capabilities of the student leaders in understanding and moving forward for the process of introducing and implementing the concept. In early 2013, the first Mesyuarat Kepimpinan Mahasiswa (MEKEM) was convened and decisions made by the student leaders were being implemented by HEP UiTMCT. This is the first notion of empowerment seen in UiTMCT.